Unveiling the transition from paleolake Lisan to Dead Sea through the analysis of lake paleoshorelines and radiometric dating of fossil stromatolites - Jara Muñoz, Julius; Agnon, Amotz; Fohlmeister, Jens; Tomás, Sara; Mey, Jürgen; Frank, Norbert; Schröder, Birgit; Schröder-Ritzrau, Andrea; Garcin, Yannick; Darvasi, Yaniv; Melnick, Daniel; Mutti, Maria; et al. (Geochemistry, geophysics, geosystems, 2024)
To date, the most complete paleolake-level reconstructions for the late Pleistocene water bodies that once occupied the Dead Sea depression have been based on the combination of dating of lake sediments and terrestrial materials. However, despite these major accomplishments, there is still limited spatial control regarding the water levels, suggesting some degree of uncertainty concerning the magnitude and rate of lake-level changes. Here, we re-examine the late Pleistocene lake-level changes in the Dead Sea during the transition from paleolake Lisan to the present-day Dead Sea. We rely on systematic dating of fossil stromatolites including 84 radiocarbon and 15 U-series ages, stable-isotope measurements, paleobiology, high-resolution topography, and numerical modeling to assess lake-level changes. Our results indicate that the highstand of paleolake Lisan was of shorter duration and the transition between Lake Lisan and the Dead Sea occurred at least 5 Kyrs earlier than previously indicated. By refining the timeline and accuracy of lake-level positions during the transition paleolake Lisan - Dead Sea, our study offers new insights into the regional and local paleo-climatic conditions during the last glacial period in this region.
Erstveröffentlichung: 5. August 2024
Gesehen am 18.08.2025